Ali vadba na ravnotežni plošči Wii z igrami Wii Fit pri bolnikih s pridobljenimi okvarami perifernih živcev vpliva na ravnotežje in hojo? - Zupanc, Aleksander (Rehabilitacija (Ljubljana), 2014)
Background: Patients with acquired peripheral lesions have balance and walking disorders. The aim of our study was to determine if training on the Wii balance board with Wii Fit games improves balance and walking in patients with acquired peripheral nerve lesions. Methods: Our observational study involved 11 patients (6 male, 5 female), aged 43.5 years on average (range 15-72 years). They performed training on the Wii balance board in addition to physiotherapy every day for 30 min per session on average, for two to six weeks. Before and after training the measurements with the Berg Balance Scale, the functional reach test, the 10-meter walk test and the 6-minute walk test were performed. Results: Post intervention measurements showed statistically significant improvements on the Berg Balance Scale for 13.8 points on average (SD 10.3), on the functional reach test for 11.0 cm on average (SD 8.4 cm), on the 10-meter walk test (in terms of speed) for 0.34 m/s on average (SD 0.18 m/s), and on the 6-minute walk test for 114 m on average (SD 61 m). All the patients achieved progress on all the clinical tests. Conclusion: The training on the Wii balance board with Wii Fit games as a supplement to physiotherapy improves balance and walking in patients with acquired peripheral nerve lesion, thus reducing their fall risk. To assess the added benefit of the training using the Wii system as compared to standard physiotherapy, a randomised controlled study would be required.
Keywords: balance training; fizioterapija; navidezna resničnost; Nintendo; physiotherapy; rehabilitacija; Rehabilitation; vadba ravnotežja; virtual reality; vocational rehabilitation